Analysis of the effect of 6‐Hz binaural beats on electroencephalographic and autonomic parameters of healthy individuals: An exploratory study - Irene Scala; Jessica Marotta; Valerio Brunetti; Filippo Del Tedesco; Rikardo Xhemalaj; Pier Andrea Rizzo; Giovanni Frisullo; Eleonora Rollo; Maria Grazia Bocci; Edoardo Piervincenzi; Giacomo Della Marca; Riccardo Maviglia (Physiological Reports)
Abstract Binaural beats (BB) are a non‐acoustic perception generated when two pure tones with a slight mismatch in frequency are presented separately to each ear. The aims of our study were to analyze the ability of 6‐Hz BB in entraining cortical activity, altering cortical connectivity, and influencing Autonomic Nervous System (ANS) functioning to evaluate, in future studies, their application in improving compliance with Non‐Invasive Ventilation (NIV) in critically ill patients. Twenty healthy volunteers underwent four 10‐min experimental auditory conditions while their electroencephalographic and polygraphic activities were recorded: Resting‐state, 6‐Hz BB, 6‐Hz monaural beats (MB), and random noise (RN). Frequency analysis and analysis of lagged‐phase connectivity were computed through eLORETA. Heart rate variability, respiratory rate, and pulse transit time were analyzed as indicators of ANS activity. 6‐Hpz BB entrained cortical activity at the beat frequency in the left cuneus and precuneus, in contrast with other experimental conditions. All auditory stimuli increased the interhemispheric lagged‐phase connectivity between auditory cortices. Contrary to MB and RN, BB induced only minimal changes in ANS parameters. 6‐Hz BB is effective in entraining cortical activity and induces only minimal changes in ANS parameters. These findings support the future use of BB as tools for increasing NIV compliance.